KREDYT OD DOSTAWCY JAKO ŹRÓDŁO POZABAN KOWEGO FINANSOWANIA PRZEDSIĘBIORSTWA. PROBLEMY OGÓLNE - Łuczka, Teresa (Wydział Prawa i Administracji UAM, 1998)
High costs of a trade credit have some serious consequences for the structure of capital of a creditor. From the point of view of remunerativeness - having recourse to the most expensive from of financing from the outside results in raising the average cost o f engaging capital by a business and, consequently, in decreasing of remunerativeness of the capital used. From the point of view of financial position of a business such a credit does increase its own payment capacity and even sometimes it becomes the only available way of getting a source financing of short-termed economic growth. Nevertheless, from the point of view of the criterion of sovereignty of a business - the trade credit has negative influence because of increased economic dependence on a deliverer and, finally, because of the fact that the business gets enforced to comply with conditions offered by the creditor.
TRADE CREDIT AS A SOURCE OF EXTRA-BANK FINANCING OF A BUSINESS. GENERAL ISSUES